Ameliorative potential of quercetin and catechin against sodium arsenite and mancozeb-induced oxidative renal damage in Wistar rats - Rasia Yousuf; Pawan Kumar Verma; Priyanka Sharma; Shilpa Sood; Abderrahmane Aït-Kaddour; Zuhaib F. Bhat (Journal of Trace Elements and Minerals, 2023)
Background: The present study aimed to determine the impact of the toxicological interaction between mancozeb (MZ) and arsenic (As) on oxidative injury to the kidney and to compare the ameliorative potential of quercetin and catechin against the induced toxicity. Methods: Sixty adult male Wistar rats were randomly and equally divided into 10 groups (n=6). Group I served as control and group II was treated with MZ [800 mg kg−1 body weight (BW), orally (PO)]. Groups III, IV, and V were exposed to As at the rate of 10, 50, and 100 ppb, respectively, in drinking water continuously for 28 days. Groups VI, VII, and VIII were provided drinking water with As at 10, 50, and 100 ppb, respectively, together with MZ for 28 days. Groups IX and X were given As in drinking water at 100 ppb and MZ at 800 mg kg−1, BW PO along with quercetin (50 mg kg−1) and catechin (50 mg kg−1), respectively. Results: Significant (P<0.05) alterations in renal biomarkers along with variations in the renal tissue antioxidant status of MZ-treated rats were seen in comparison to the control. The exposure to As also affected these biomarkers in a dose-dependent manner. Co-exposure to the toxicants potentiated oxidative renal damage which was also confirmed by histopathological findings. Administration of quercetin or catechin concurrently with the toxicants markedly alleviated the alterations in biochemical and oxidative biomarkers and renal tissue architecture. Conclusion: The present study increased our understanding of the toxicological interaction between MZ and As and its impact on oxidative damage to the kidney. The study also demonstrated the ameliorative potential of quercetin and catechin against induced toxicity. The results of the study demonstrated the better ameliorative potential of quercetin in comparison to catechin in MZ and As-induced renal toxicity in Wistar rats.